Merdeka Belajar approach: a strategy to foster enjoyable learning experiences in higher education - Salsabila Maghfira; Eka Kurnia Darisman; Riga Mardhika (Sriwijaya Journal of Sport, 2025)
Research Problems: The Merdeka Belajar approach allows students to choose learning methods that align with their interests and needs. This approach will enhance motivation and create a more enjoyable learning environment. Research Objectives: This study aims to examine the impact of the Merdeka Belajar concept on students' level of enjoyment in Sports Psychology classes. Methods: This research employs a quantitative approach using a survey technique. Questionnaires were distributed to students enrolled in the Sports Psychology course. The data were analysed using descriptive and inferential statistical techniques. Results: The Merdeka Belajar concept positively contributes to students' enjoyment, with a correlation value of (r = 0.78, p < 0.05). This indicates that the higher the implementation of the Merdeka Belajar concept, the higher the students' enjoyment in attending lectures. Additionally, regression analysis shows that Merdeka Belajar contributes 61% to the increase in students' enjoyment, while the remaining percentage is influenced by other factors such as the learning environment and individual interest. Conclusion: The implementation of Merdeka Belajar can be an effective strategy for creating a more enjoyable lecture environment and enhancing students' psychological well-being.